E-learning Assissted by Finger Printing on Students’ Critical Thinking and Creativity - Rati, Ni Wayan; Rediani, Ni Nyoman (Universitas Pendidikan Ganesha, 2020)
The impact of covid-19 requires all types of learning activities to be carried out online. The long online learning process results in boredom among students so that the online learning process is not optimal. The research objective was to analyze the effect of e-learning assisted by finger painting on critical thinking skills and student creativity. This type of research is quasi-experimental research, the design of this study used a posttest only control group design. The study population was 180 students in semester III who received basic science concepts courses. The data collection methods used were test and non-test. This study uses two analytical techniques,Â descriptive analysis, and inferential analysis. Inferential analysis is used to test the research hypothesis. Before analyzing inferential data, the data is tested for normality and homogeneity. In this study, the inferential analysis was assisted by using SPSS 17.00. The results of this research can be said that with the effect of e-learning assisted by finger painting on the critical thinking and creativity abilities of PGSD students, this can be seen from the Manova test results that the resulting significant score is less than 0.05,Â 0.00. So it can be said that e-learning assisted by finger painting impacts critical thinking and creativity, critical thinking, and PGSD students' creativity.